Commitment of Budget Planning and SPIP Moderating Organizations to Budget Absorption - Ayem, Sri; Purwanto, Tomi (Universitas Kristen Maranatha, 2024)
Purpose -The purpose of this study was to determine whether budget absorption is increased through budget planning. To determine whether budget absorption is increased by the government's internal control system, to determine whether organizational commitment can increase budget absorption while reducing the impact of budget planning, to determine the possibility that organizational commitment can mitigate the benefits of the government's internal control system on budget absorption. Design/methodology/approach - Data collection using a questionnaire with a research sample of 90 respondents. The data analysis tool used multiple regression with the F test and t test. Findings - The findings of the analysis indicate that organizational commitment can mitigate the impact of budget planning and the government's internal control system on budget absorption. Budget planning has a negative impact on budget absorption, while the government's internal control system has a positive impact. Research limitations/implications - The conclusion of this study is to describe the theoretical implications by adding new literature and insights into regional finances and providing ideas for further research so that the Kulon Progo Regency OPD can improve its ability to maximize the budget planning that has been prepared and implement the government's internal control system effectively, efficiently and sustainably so that all organizational goals, especially budget absorption, can run well proportionally every quarter. And budget absorption at the end of the year, can be achieved according to target. Keywords: Budget Absorption, Government Internal Control System, Organizational Commitment